2019
DOI: 10.1016/j.kint.2018.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin links oxidative stress to podocyte injury and proteinuria

Abstract: Podocyte injury is the major cause of proteinuria in primary glomerular diseases. Oxidative stress has long been thought to play a role in triggering podocyte damage; however, the underlying mechanism remains poorly understood. Here we show that the Wnt/b-catenin pathway is involved in mediating oxidative stress-induced podocyte dysfunction. Advanced oxidation protein products, a marker and trigger of oxidative stress, were increased in the serum of patients with chronic kidney disease and correlated with impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 46 publications
1
108
1
Order By: Relevance
“…β‐catenin is the downstream effector of Wnt signalling in tubular cell senescence, podocyte dedifferentiation and fibroblast activation . Although β‐catenin expression is silent in normal adult kidneys, it is reactivated at an early stage and keeps activation in the progression of CKD .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…β‐catenin is the downstream effector of Wnt signalling in tubular cell senescence, podocyte dedifferentiation and fibroblast activation . Although β‐catenin expression is silent in normal adult kidneys, it is reactivated at an early stage and keeps activation in the progression of CKD .…”
Section: Discussionmentioning
confidence: 99%
“…Protein expression levels were analysed by Western blot analysis as described previously . The primary antibodies used were as follows: anti‐SDF‐1α (ab25117; Abcam), anti‐fibronectin (F3648; Sigma‐Aldrich), anti‐α‐SMA (ab5694; Abcam), anti‐collagen I (ab34710; Abcam), anti‐vimentin (SAB1305447, Sigma‐Aldrich), anti‐CXCR4 (BA0747‐2; Boster), anti‐p‐GSK3β (ser 9) (5558; Cell Signaling Technology), anti‐β‐catenin (610 154; BD Transduction Laboratories), anti‐PAI‐1 (AF3828; R&D Systems), anti‐snail1 (ab180714; Abcam), anti‐MMP‐7 (104 658; GTX), anti‐E‐cadherin (3195; Cell Signaling Technology), anti‐active β‐catenin (19807s; Cell Signaling Technology), anti‐Kim1 (BA3537; Boster, Wuhan, China), anti‐α‐tubulin (RM2007, Ray Antibody Biotech, Beijing, China) and p‐STAT antibody sampler kit (9914; Cell Signaling Technology), p‐JAK family antibody sampler kit (97 999; Cell Signaling Technology), STAT antibody sampler kit (9939; Cell Signaling Technology) and anti‐GAPDH (RM2000, Ray Antibody Biotech, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify the upstream signal responsible for Shh induction in podocytes, we examined the potential role of Wnt ligands using cultured podocytes in vitro, because earlier studies showed that this signal cascade is activated in podocytes after injury (22,23). As shown in Figure 1, D and E, multiple Wnt ligands, either alone or in combination, induced Shh expression in cultured mouse podocytes.…”
Section: Resultsmentioning
confidence: 99%